El juego como estrategia metodológica en la enseñanza del miniatletismo de los estudiantes varones del nivel básico superior de la unidad educativa Manuel Ignacio Monteros ciudad de Loja. Periodo 2014-2015 - Saraguro Jaramillo, Angel David (2016)
This research entitled: The game as a methodological strategy in teaching male students miniatletismo upper basic level of the Education Unit City Loja "Manuel Ignacio Monteros." Period 2014-2015; whose problem arises How affects the game as a methodological strategy in teaching students miniatletismo in upper basic level? It had as its main objective to determine the teaching and learning processes used by teachers in teaching athletics Mini male students of the upper basic level. The specific objectives; Analyze the methodological strategies used by teachers to teach Mini Athletics male students of Superior basic level, design a set of games as a methodological strategy to teach male students miniatletismo Upper Basic Level, Apply a set of games as a methodological strategy to teach male students Miniatletismo of Upper Basic Level and evaluate a set of games as a methodological strategy to teach male students miniatletismo Upper Basic Level. As we review literature category I: The Game and Category 2: Mini Athletics. The research design is Pre-Experimental, methods used in the research were: scientific, inductive and descriptive, the results are structured in tables and graphs and analysis thereof which are the result of the application of techniques and instruments such as the observation guide children and teachers survey. The results are in tables and graphs with their analysis, the argument is an array of negative situation and a positive situation with their respective analysis, after analyzing the results of instruments, it came to the conclusion that the game application as a methodological strategy if successful strikes in teaching mini athletic male students in upper basic level. As far as physical education teachers recommend using games in their lessons mini athletics and in all situations, because the game is not only fun but also a methodological strategy for children's learning. The alternative proposal we set for this research is titled Program methodological games for teaching mini athletics.